2014
DOI: 10.1007/s10509-014-2067-8
|View full text |Cite
|
Sign up to set email alerts
|

Solar activity during first six years of solar cycle 24 and 23: a comparative study

Abstract: Attempt to look into the nature of solar activity and variability have increased importance in recent days because of their terrestrial relationships. In the present work we have attempted to compare the solar activity events during first six years (2008-2013) of the ongoing solar cycle 24 with first six years (1996-2001) of solar cycle 23. To that end, we have considered sunspot numbers, F10.7 cm solar flux, halo CMEs and geomagnetic storms as comparison parameters. Sunspot number during the year 2008-2013 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This suggests that solar cycle 24 is weaker than 23. Many authors also showed that solar cycle 24 is weaker than 23 (Richardson 2013;Singh et al 2014;Kakad et al 2019). It is supposed that the weak polar fields observed during the solar activity minimum period of solar cycle 23 are the main cause of the weakness of the solar cycle 24 (Jiang et al 2015).…”
Section: B Association Of Solar Flares With Super Active Regions (Sars)mentioning
confidence: 99%
“…This suggests that solar cycle 24 is weaker than 23. Many authors also showed that solar cycle 24 is weaker than 23 (Richardson 2013;Singh et al 2014;Kakad et al 2019). It is supposed that the weak polar fields observed during the solar activity minimum period of solar cycle 23 are the main cause of the weakness of the solar cycle 24 (Jiang et al 2015).…”
Section: B Association Of Solar Flares With Super Active Regions (Sars)mentioning
confidence: 99%
“…Here OSIRIS Na data are daily averaged over the tropics (27° S–27° N) from 2004 to mid‐2013, spanning portions of solar cycles 23 and 24. Although the solar cycle 24 is unusually quiet (e.g., Singh & Tonk, ), observations can still be used to test the model result.…”
Section: Data Description and Analysismentioning
confidence: 99%